Telemedicine and Telehealth in Urology—What Do the ‘Patients' Think About It? - Naik, Nithesh; Hameed, B. M. Zeeshan; Nayak, Sanjana Ganesh; Gera, Anshita; Nandyal, Shreyas Raghavan; Shetty, Dasharathraj K.; Shah, Milap; Ibrahim, Sufyan; Naik, Aniket; Kamath, Nagaraj; Mahdaviamiri, Delaram; D'costa, Kenisha Kevin; et al. (Frontiers in Surgery, 2022)
Telemedicine is the delivery of healthcare to patients who are not in the same location as the physician. The practice of telemedicine has a large number of advantages including, cost savings, low chances of nosocomial infection, and fewer hospital visits. Tele clinics have been reported to be successful in the post-surgery and post-cancer therapy follow-up and providing consultative service for the evaluation of patients with urolithiasis. This review focuses to identify the outcomes of the recent studies related to the use of video consultations in urology clinics for haematuria referrals as well as follow-up visits for a variety of illnesses, including benign prostatic hyperplasia (BPH), kidney stone disease (KSD), and urinary tract infections (UTIs) and found that they are highly acceptable and satisfied. Certain medical disorders can lead to feelings of humiliation, social isolation, and low self-esteem, all of which can negatively impair health-related quality of life. Telemedicine has proven to be beneficial in such patients and a reliable, cost-effective patient-care tool, and it has been successfully implemented in various healthcare settings and specialties.